STUDENT'S ABILITY IN EXPLAINING THE CONCEPT OF SOLID FIGURE'S VOLUME REVIEWED FROM VISUALIZER VERBALIZER COGNITIVE STYLE - Rohmah Indahwati; Fetty Nuritasari (USN Kolaka, 2022)
The purpose of this study was to describe student's ability to explain the concept of solid figure's volume reviewed from visualizer-verbalizer cognitive style using the Cognitive Style Test developed by Mendelson & Thorson. This study used a qualitative approach and the data collection technique was carried out by giving tests about the concept of solid figure's volume and interviews. The indicators used to measure students' ability to explain the concept of solid figure's volume are, (1) Providing information in accordance with mathematical concepts (2) Information systematically organized with the aim of showing a mathematical relationship (3) using and selecting procedures or operations certain exactly. The results showed that both visualizer subjects (SV) and verbalizer subjects (SB) were only able to fulfill the first indicator in explaining the concept, both of them just can mention the formula of pyramid's volume. Meanwhile, to explain the concept of ball's volume, SV does not meet the third indicator, SV did not use the right mathematical procedures or operations. Both subjects showed characteristics that matched their cognitive style, namely SV was more flexible in providing explanations through pictures and SB preferred to make explanations in the form of descriptions.